Heat wave occurrences over Senegal during spring: Regionalization and synoptic patterns. (31st July 2019) - Sambou, Marie‐Jeanne G.; Janicot, Serge; Pohl, Benjamin; Badiane, Daouda; Dieng, Abdou Lahat; Gaye, Amadou
Abstract: Based on 12 Senegalese stations of the Global Summary of the Day (GSOD) database (1979–2014), heat waves (HW) are defined for each station in spring (March–April–May, the hottest season in Senegal) as the daily maximum temperature (Tx), minimum temperature (Tn), or average apparent temperature of the day (AT), exceeding the corresponding 95% mobile percentile for at least three consecutive days. A hierarchical cluster analysis used to regionalize HW in these 12 stations is applied to simultaneous occurrences of daily temperature peaks over their 95% mobile percentiles. Three homogeneous zones of four stations each are identified (Zone 1, Zone 2 and Zone 3), from west (Atlantic coastline) to east (inland Senegal). Atmospheric circulation associated with HW is assessed through composites of ERA‐Interim deseasonalized anomalies, with the start date of each HW in each zone used as a reference. The main pattern controlling the presence of HW in Senegal consists in positive pressure anomalies centred around the strait of Gibraltar, promoting easterly to northeasterly wind anomalies. This causes higher temperatures in the three zones of Senegal, and lower temperatures and drier air over the central Sahel. This pattern is opposite to that characteristic of HW in the central Sahel shown in previous studies. From Zone 1 to Zone 3, the temperature and moisture patterns are shifted to the east while pressure anomalies weaken drastically. Night‐time Tn‐HW are characterized by higher water vapour contents than daytime Tx‐HW, corroborating and complementing previous studies over the Sahel. These HW patterns are close to the canonical mode of intra‐seasonal atmospheric variability over Senegal. Abstract : Senegal has specific heat wave patterns compared to the rest of the Sahel. Regarding heat wave occurrences, three zones (coastal, eastern/continental and intermediate) can be differentiated in Senegal. A general circulation pattern, characterized by anticyclonic high‐pressure anomalies over the strait of Gibraltar, controls heat wave occurrences over Senegal.